2022
DOI: 10.3847/psj/ac91cc
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Impact and Target Parameters on the Results of a Kinetic Impactor: Predictions for the Double Asteroid Redirection Test (DART) Mission

Abstract: The Double Asteroid Redirection Test (DART) spacecraft will impact into the asteroid Dimorphos on 2022 September 26 as a test of the kinetic impactor technique for planetary defense. The efficiency of the deflection following a kinetic impactor can be represented using the momentum enhancement factor, β, which is dependent on factors such as impact geometry and the specific target material properties. Currently, very little is known about Dimorphos and its material properties, which introduces uncertainty in t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 167 publications
4
31
0
Order By: Relevance
“…Our result for 𝛽 is consistent with numerical simulations [11][12][13][14][15][16][17][18][19][20][21] and laboratory experiments [22][23][24][25][26][27][28] of kinetic impacts, which have consistently indicated that 𝛽 is expected to fall between about 1 and 6. However, non-unique combinations of asteroid mechanical properties (e.g., cohesive 5 strength, porosity, and friction angle) can produce similar values of 𝛽 in impact simulations 18 . Future studies that combine estimates of 𝛽 with additional constraints from the DART impact site geology 1 and ejecta observations 3,4 will provide greater insight into Dimorphos's material properties.…”
supporting
confidence: 89%
“…Our result for 𝛽 is consistent with numerical simulations [11][12][13][14][15][16][17][18][19][20][21] and laboratory experiments [22][23][24][25][26][27][28] of kinetic impacts, which have consistently indicated that 𝛽 is expected to fall between about 1 and 6. However, non-unique combinations of asteroid mechanical properties (e.g., cohesive 5 strength, porosity, and friction angle) can produce similar values of 𝛽 in impact simulations 18 . Future studies that combine estimates of 𝛽 with additional constraints from the DART impact site geology 1 and ejecta observations 3,4 will provide greater insight into Dimorphos's material properties.…”
supporting
confidence: 89%
“…Impact simulations conducted in preparation for DART’s kinetic impact test indicated that, depending on the material strength, impact conditions and other properties, the value of the momentum enhancement factor, β , could be considerable, with predicted values as high as 5 (ref. 2 ) or 6 (ref. 3 ), with a resulting orbital period change of more than 40 min (ref.…”
Section: Mainmentioning
confidence: 99%
“… The Double Asteroid Redirection Test (DART) spacecraft successfully performed the first test of a kinetic impactor for asteroid deflection by impacting Dimorphos, the secondary of near-Earth binary asteroid (65803) Didymos, and changing the orbital period of Dimorphos. A change in orbital period of approximately 7 min was expected if the incident momentum from the DART spacecraft was directly transferred to the asteroid target in a perfectly inelastic collision 1 , but studies of the probable impact conditions and asteroid properties indicated that a considerable momentum enhancement ( β ) was possible 2 , 3 . In the years before impact, we used lightcurve observations to accurately determine the pre-impact orbit parameters of Dimorphos with respect to Didymos 4 6 .…”
mentioning
confidence: 99%
“…A key parameter that the DART mission aimed to measure is the momentum gain factor (β ), defined as the momentum change of the asteroid divided by the momentum of the impactor. This resulted in a large effort to predict the outcome of the DART impact 4,5,7,20 . Since only 1/6 of NEOs are binary systems (such as the Didymos system), it is essential to develop methods to estimate the momentum gain of non-binary asteroids in a timely manner, using ground-based observations of the impact ejecta.…”
Section: /21mentioning
confidence: 99%
“…
The Double Asteroid Redirection Test 1, 2 (DART) was intended to test planetary defense strategies via the reaction of the near-Earth asteroid Dimorphos, a satellite of Didymous, to a spacecraft impact. Pre-impact modeling [3][4][5][6][7] predicted a momentum gain of the impacted asteroid in the range of 1 − 5 times that of the impactor. These models further suggest that the velocity distribution of the ejecta depends, for example, on the material cohesion and porosity.
…”
mentioning
confidence: 99%